The molecular basis for rRNA-dependent spectinomycin resistance in Nicotiana chloroplasts - Fromm, Hillel (1987)
The chloroplast genes coding for the 16S ribosomal RNA from several spectinomycin-resistant Nicotiana mutants were analyzed. Two classes of mutants were identified. In one class, a G to A base transition is found at position 1140 of the tobacco-chloroplast 16S rRNA gene, which eliminates an AatII restriction endonuclease site. This base transition is proximal to a mutation previously described for spectinomycin resistance in Escherichia coli. In the other class, a novel G to A transition is found at position 1012 of the 16S rRNA gene. Although the mutations in the two classes are 128 nucleotides apart, the secondary structure model for 16S rRNA suggests that the two mutated nucleotides are in spatial proximity on opposite sides of a conserved stem structure in the 3' region of the molecule. Phylogenetic evidence is presented linking this conserved stem with spectinomycin resistance in chloroplasts. Perturbation of the stem is proposed to be the molecular-genetic basis for rRNA-dependent spectinomycin resistance.